Prevalence and Risk Factors for Presumptive Ascending/Descending Myelomalacia in Dogs after Thoracolumbar Intervertebral Disk Herniation - F. Balducci; S. Canal; B. Contiero; M. Bernardini (Journal of Veterinary Internal Medicine, 2017)
Background Ascending/descending myelomalacia (ADMM) is a severe complication of thoracolumbar intervertebral disk herniation (TL‐IVDH) in dogs. Hypothesis/Objectives To investigate the prevalence and risk factors for ADMM in nonambulatory dogs with surgically treated TL‐IVDH. Animals Six‐hundred and fifty‐two client‐owned dogs evaluated for TL‐IVDH that underwent decompressive spinal surgery. Methods Retrospective medical record review from February 2007 through December 2015. Results Thirteen dogs developed ADMM, with an overall prevalence of 2.0%. The prevalence of ADMM was 0% in dogs with neurological signs graded 1 or 2 at admission or before magnetic resonance imaging (MRI) or surgical procedures, 0.6% in dogs with neurological signs graded 3, 2.7% in dogs with neurological signs graded 4, and 14.5% in dogs with neurological signs graded 5. Age (<5.8 years), neurological status (grade 5), site of disk herniation (L5‐L6), duration of clinical signs before becoming nonambulatory (<24 hours), detection of intramedullary T2‐weighted (T2W) hyperintensity, and a T2 length ratio >4.57 were significant risk factors in the univariate analysis for development of ADMM. Conclusions and Clinical Importance The factors identified in this study may be useful for the prediction of ADMM. Multicenter studies with a higher number of dogs with ADMM are required to confirm these data.